2015
DOI: 10.1111/bjd.13756
|View full text |Cite
|
Sign up to set email alerts
|

The role ofBRAFmutations in primary melanoma growth rate and survival

Abstract: The presence of a BRAF mutation does not necessarily 'drive' more rapid tumour growth but is associated with poorer MSS in patients with early-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
(62 reference statements)
2
29
1
Order By: Relevance
“…Nonetheless, this tendency to shorter survival in V600K subjects is consistent with literature findings that V600K tumors tend to have less favorable outcomes than V600E tumors [4, 811, 13]. …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, this tendency to shorter survival in V600K subjects is consistent with literature findings that V600K tumors tend to have less favorable outcomes than V600E tumors [4, 811, 13]. …”
Section: Resultssupporting
confidence: 91%
“…Patients with V600K tumors appear to be older (over 50) males, and the tumors often occur in the head and neck area (prone to sun damage) [4, 713]. Pathologically, V600K tumors appear to be thicker and are more mitotically active than V600E tumors [8]. Clinically, patients with V600K tumors have an increased risk for brain and lung metastases and are at a siginficantly increased risk of relapse and have a shorter time from diagnosis to metastasis than those with V600E tumors [4, 811, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRAF V600E mutation has been identified in 40% to 45% of metastatic melanomas in prospective studies with comprehensive interrogation (23,24). This mutation is considered an oncogenic driver, and melanomas bearing these BRAF V600E alterations have excellent responses to BRAF inhibitors such as vemurafenib or dabrafenib (26,27); these responses are entirely comparable with the most effective single-agent, oncogene-targeted therapies in non–small lung cancer (EGFR and ALK inhibitors in patients with corresponding actionable alterations) (33–36).…”
Section: Brafmentioning
confidence: 99%
“…[11,12] These oncogenic drivers in the NRAS Q61K promote invasiveness of the malignant cells and have larger nodal involvement when compared to the BRAF mutations. [13] RXRα plays a major role in gene expression and signal transduction and in human melanomas the expression of RXRα is lost as the disease progresses. [14] Animal studies have indicated that the loss of RXRα in skin keratinocytes can lead to the increased melanocyte proliferation and the formation of malignant melanomas.…”
Section: Introductionmentioning
confidence: 99%